2016
DOI: 10.15625/0866-7136/38/2/7066
|View full text |Cite
|
Sign up to set email alerts
|

Postbuckling of thick FGM cylindrical panels with tangential edge constraints and temperature dependent properties

Abstract: Abstract. This paper investigates postbuckling behavior of thick FGM cylindrical panels resting on elastic foundations and subjected to thermal, mechanical and thermomechanical loading conditions. Material properties are assumed to be temperature dependent, and graded in the thickness direction according to a simple power law distribution in terms of the volume fractions of constituents. Governing equations are based on higher order shear deformation shell theory incorporating von Karman-Donnell geometrical no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Unlike flat plate and circular cylindrical shells, due to curved configuration, membrane prebuckling state cannot exist. Previous studies [27][28][29] indicated that thermally loaded FGM curved panels with perfect geometry and immovable edges are monotonically deflected at the onset of heating. Linear and nonlinear buckling analyses of FG-CNTRC cylindrical panels under uniform temperature rise have been performed by Mehar et al [30] and Shen and Xiang [31] employing numerical and semi-analytical approaches, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike flat plate and circular cylindrical shells, due to curved configuration, membrane prebuckling state cannot exist. Previous studies [27][28][29] indicated that thermally loaded FGM curved panels with perfect geometry and immovable edges are monotonically deflected at the onset of heating. Linear and nonlinear buckling analyses of FG-CNTRC cylindrical panels under uniform temperature rise have been performed by Mehar et al [30] and Shen and Xiang [31] employing numerical and semi-analytical approaches, respectively.…”
Section: Introductionmentioning
confidence: 99%